A Study of Project Finance Risk- Returns Relationship of Indian Power Projects – from an Investor Perspective - Das, Sampuran (2010)
This study is motivated by need for financing India’s huge infrastructure gap. Given that infrastructure assets are heterogeneous – this study focuses on power projects. Firstly the study examines whether the current regulatory environment is conducive for attracting large scale investments, since the country has a checkered past in light of Enron fiasco, during the 1990’s. Secondly, global fund managers, tends to make allocation of capital based on relative attractiveness of power sector on a regional basis – thus a comparative study of Asian peer group has been conducted. Thirdly, Project finance is characterized by long gestation period, high leverage and non-recourse financing – thus this study undertakes a credit risk analysis of key power sector companies, and thereby indentifies nature of risk lenders may be exposed to in case of a potential investment into the sector. Fourthly, the dearth of a quantitative risk framework for project finance has led to attempts for modeling uncertainty related to project’s cash flow or NPV using Monte Carlo Simulation techniques. This study applies Monte Carlo simulation of cash flows to depict value at risk (VAR) for a hypothetical (1000 MW)Greenfield power project. This can also depict scenarios in which – cash flows from operations may be inadequate to service debt. Currently – only Merton’s options pricing model is widely used to determine credit spread or risk neutral probability of default. Further the study indentifies sources of cash flow risk, and incorporates realistic values for such parameters based on case study of NTPC power plants and regulatory guidelines. The study finds that, the risk-return trade of Indian power sector investments compares favorably with respect to, the actual returns generated by listed Infrastructure Funds. Further research into alternative measure of risk and its implications for credit spread, debt pricing and leverage, would be useful for future investors.